Pulmonary alveolar proteinosis and Mycobacterium abscessus lung infection related to ruxolitinib after allogeneic stem cell transplantation. Issue 5 (31st May 2018) - Salvator, Hélène; Berti, Enora; Catherinot, Emilie; Rivaud, Elisabeth; Chabrol, Alexandre; Nguyen, Stephanie; Zemoura, Leila; Cardot, Emilie; Tcherakian, Colas; Couderc, Louis-Jean
Non-infectious pulmonary complications are frequent after allogeneic haematopoietic stem cell transplantation (HSCT). They mainly comprise bronchiolitis obliterans and interstitial pneumonia in the setting of chronic graft- versus -host disease (cGVHD) [1]. Ruxolitinib may induce pulmonary alveolar proteinosis and favour respiratory non-tuberculous mycobacterial infections http://ow.ly/bTXn30jogC8